UNAN-Managua 2013-2021 curricular plans: analysis within the framework of continuity from degree to postgraduate - Murillo Reyes, Henry Alexander; Escobar Soriano, Álvaro Antonio (Torreon Universitario Magazine, 2023)
It is unquestionable that the Higher Education system in Nicaragua and, especially, at UNAN-Managua has been experiencing changes in its curricular management, vision, mission, values ​​and work axes, which generates new and challenging scenarios. One of those is the transformation into a degree and, therefore, this implies improvement in postgraduate careers. For this, it was necessary to carry out a documentary analysis of the curricular designs of the undergraduate courses (2013 and 2021 plans) and identify how continuity occurs in undergraduate and graduate training. The objective was to analyze the main conceptual elements of the curricular plans of the UNAN-Managua courses within the framework of the continuity from undergraduate to postgraduate. The research was carried out using a qualitative approach, a major unit of analysis was identified: the continuity of the degree in the postgraduate degree, and minor ones: conceptual elements of the 2013 and 2021 curricular plans based on the continuity of degree training in the postgraduate degree; curricular improvement and linking degree to postgraduate degree. For data analysis, a double entry matrix was created. Also, information triangulation was applied, considering the objectives, research questions and units of analysis. This article presents a description of essential elements of both plans from a central perspective; elements that unite and disagree, application in daily activities or curricular management and its relationship with postgraduate careers, as well as the coherence between the training and research processes in relation to the continuity of competencies from undergraduate to postgraduate and the development of lines research at both levels.